Managing human resource in the rural tourism sector: evidence from Indonesia - Bambang Tri Harsanto (Cogent Business & Management)
The potential of rural tourism to contribute to economic and social development in Indonesia has been limited by challenges related to human resources. This study aimed to identify the primary obstacles and deficiencies in skills hindering tourism growth in villages and develop strategies focused on developing human capital. Using a qualitative methodology, data was collected through a qualitative survey of 85 representatives from local tourism associations in an emerging tourism region of Indonesia. An analysis of the responses identified significant deficiencies in marketing, digital literacy, and tourism product management skills. Other obstacles include insufficient financial resources and local attitudes that resist change and new ideas. The findings emphasize the necessity of implementing specialized training programs, providing incentives for employment in the tourism industry, and conducting awareness campaigns. A crucial proposal is to establish a strategic framework that prioritizes improving human resources through targeted capacity building for improving rural tourism. This imperative study establishes the groundwork for developing rural tourism policies and interventions by investing in human capital. The approach prioritizes the well-being of individuals and provides a model for developing rural tourism economies.